Conceptualization of a hybrid machine combining Laser Beam Micro Machining (LBMM) and Micro Electrical Discharge Machining (Micro-EDM) in a single setup - Wan Azhar, Wan Ahmad; Saleh, Tanveer (IEEE Xplore, 2024)
The utilization of hybrid laser beam micromachining (LBMM) in conjunction with micro electrical discharge machining (μEDM) has gained widespread popularity due to its ability to improve material removal rates and enhance surface quality. Typically, these processes occur on separate machines, resulting in drawbacks such as time loss during workpiece transfer, potential misalignment issues, and increased risks of sample damage during the transfer. This research provides a system and method for a two-step sequential machining process of LBMM and μEDM that allows the workpiece to remain at the same location for both processes. A LBMM process is used for drilling a rough blind hole, followed by μEDM for the finishing process. The workpiece is fixed and positioned in the μEDM workstation. A microscopic camera, which is mounted on the μEDM machine, is used to provide common coordinate position data for the laser and μEDM machine. This coordinate is used by the μEDM machine to position the electrode perfectly on top of LBMM hole before machining. The results suggest that LBMM-μEDM machining can reduce machining time while achieving good hole quality and repeatability. The hybrid sequential process significantly reduces drilling time, being about 1.55 times faster than the pure μEDM method. However, the findings also indicate that it is not necessary to use LBMM- μEDM for low aspect ratio holes. This concept enables the workpiece to stay in one position throughout both processes, eliminating any time loss and damage during transfer, as well as avoiding misalignment issues.